MENGENAL KECERDASAN, PENGETAHUAN DAN KEBIJAKSANAAN FIRMAN DALAM KONTEKS PENGENALAN AKAN ALLAH (Tinjauan Hermeneutik Amsal 1:4 dan Yohanes 1:1) - Alfrid Mali; Gregorius Tri Wardoyo (Aggiornamento, 2022)
This paper is a hermeneutic review of scripture texts, especially the book of Proverbs 1:4 and the Gospel of John 1:1. Hermeneutics or the art of interpretation or the art of searching for messages is a journey of the human mind in search of meaning. The text of the holy book is rich in meaning that should be explored to increase knowledge and faith information for humans. In the book of Proverbs 1:4 and the Gospel of John 1:1 it has meaning for the reader to know God through intelligence, knowledge and wisdom of the Word. All intelligence, knowledge and wisdom comes from God which is worthy of being lived by humans. This discussion describes the two biblical texts and explores the meaning of the text with its implications for the appreciation of faith and knowledge of God. The relevance of this paper is specifically for candidate of priests to appreciate the text of the book as a process of knowing God. As a candidate of priest, it is necessary to live the intelligence, knowledge and wisdom of the words in the scriptures to be able to cultivate personally as an intelligent, knowledgeable and wise person. Candidate of priests in the formation period is a time of personality formation to become better like Christ who is intelligent, knowledgeable and wise